Sexual Reproduction via a 1-Aminocyclopropane-1-Carboxylic Acid-Dependent Pathway Through Redox Modulation in the Marine Red Alga Pyropia yezoensis (Rhodophyta) - Uji, Toshiki; Endo, Harune; Mizuta, Hiroyuki (Frontiers in Plant Science, 2020)
The transition from the vegetative to sexually reproductive phase is the most dynamic change to occur during a plant’s life cycle. In the present study, we showed that the ethylene precursor 1-aminocylopropane-1-carboxylic acid (ACC) induces sexual reproduction in the marine red alga Pyropia yezoensis independently from ethylene. Exogenous application of ACC, which contains a three membered carbocyclic ring, promoted the formation of spermatia and carporspores in gametophytes, whereas ethephon, an ethylene-releasing compound, did not stimulate sexual reproduction. In addition, an ACC analog, 1-aminocyclobutane-1-carboxylic acid (ACBC), which contains a four membered carbocyclic ring, promoted sexual reproduction and enhanced tolerance to oxidative stress in the same manner as ACC, but 1-aminocyclopentane-1-carboxylic acid (cycloleucine; which contains a cyclopentane ring) did not. The application of ACC increased the generation of reactive oxygen species (ROS) and induced the expression of PyRboh gene encoding NADPH oxidase. ACC also stimulated the synthesis of ascorbate (AsA) by inducing transcripts of PyGalLDH, which encodes galactono-1,4-lactone dehydrogenase, the catalyst for the final enzymatic step of the AsA biosynthetic pathway. Conversely, ACC caused a decrease in the synthesis of glutathione (GSH) by repressing transcripts of PyGCL, which encodes glutamate cysteine ligase, the catalyst for the rate-limiting step in the formation of GSH. These results suggest a possible role played by ACC as a signaling molecule independent from ethylene in the regulation of sexual reproduction through alterations to the redox state in P. yezoensis.